The Gown-glove Interface Is a Source of Contamination: A Comparative Study - Fraser, James F. (Clin Orthop Relat Res, 2014)
BACKGROUND: The original Charnley-type negative-pressure body exhaust suit reduced infection rates in randomized trials of total joint arthroplasty (TJA) decades ago. However, modern positive-pressure surgical helmet systems have not shown similar benefit, and several recent studies have raised the question of whether these gowning systems result in increased wound contamination and infections. The gown-glove interface may be one source of particle contamination. QUESTIONS/PURPOSES: The purpose of this study was to compare particle contamination at the gown-glove interface in several modern surgical helmet systems and conventional surgical gowns. METHODS: A 5-μm fluorescent powder was evenly applied to both hands to the level of the wrist flexion crease. After gowning in the standard fashion, the acting surgeon performed a 20-minute simulated TJA protocol. Each of the five gowning systems was run through five trials. The amount of gown contamination at the gown-glove interface then was measured by three observers under ultraviolet light using a grading scale from 0 (no contamination) to 4 (gross contamination). Statistical analysis was carried out with Minitab 15. Friedman’s test was used to compare the levels of contamination across trials for each gown and the Mann-Whitney test was used post hoc to perform a pairwise comparison of each gown. RESULTS: All gown-glove interfaces showed some contamination. Friedman’s test showed that there was a significant difference in contamination between gowns (p = 0.029). The Stryker T5 Zipper Toga system showed more contamination than the other gowns. The median contamination score and range for each gowning setup was 1.8 (range, 1–4; conventional Kimberly-Clark MicroCool gown without helmet), 4 (range, 3–4; Stryker T5 Zipper Toga), 3.6 (range, 0–4; Stryker helmet with conventional gown), 1.6 (range, 0–2; Stryker Flyte Toga), and 3.0 (range, 2–3; DePuy Toga). A Mann-Whitney test found no difference among any of the gowns except for the Stryker T5 Zipper Toga, which showed more contamination compared directly with each of the other four gowns (p < 0.001 for each gown-to-gown comparison). CONCLUSIONS: Particle contamination occurs at the gown-glove interface in most commonly used positive-pressure surgical helmet systems. The Stryker T5 Zipper Toga exhibited more contamination than each of the other gowning systems. CLINICAL RELEVANCE: The gown-glove interface is prone to particle contamination and all surgeons should be aware of this area as a potential source of surgical site infection. Although future studies are needed to clarify the link between particle contamination through this route and clinical infection, surgeons should consider using gowning systems that minimize the migration of fomites through the gown-glove interface. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-014-4094-8) contains supplementary material, which is available to authorized users.